2009
DOI: 10.1007/s00167-009-0777-1
|View full text |Cite
|
Sign up to set email alerts
|

Tibiofemoral kinematic analysis of knee flexion for a medial pivot knee

Abstract: The performance of total knee arthroplasty in deeply flexed postures is of increasing concern as the procedure is performed on younger, more physically active and more culturally diverse populations. Several implant design factors, including tibiofemoral conformity, tibial slope and posterior condylar geometry have been shown directly to affect deep flexion performance. The goal of this study was to evaluate the kinematics of a fixed-bearing, asymmetric, medial rotation arthroplasty design in moderate and deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 35 publications
2
36
0
Order By: Relevance
“…ROM after TKA using a medial pivot knee system designed based on the concept of medial-pivoting of the knee during flexion21,22) has been documented in a variety of domestic and international research23-29). The mean maximal flexion angle of 118.44° that was obtained in our patients is comparable to the values reported in those studies.…”
Section: Discussionsupporting
confidence: 83%
“…ROM after TKA using a medial pivot knee system designed based on the concept of medial-pivoting of the knee during flexion21,22) has been documented in a variety of domestic and international research23-29). The mean maximal flexion angle of 118.44° that was obtained in our patients is comparable to the values reported in those studies.…”
Section: Discussionsupporting
confidence: 83%
“…Consequently, this provides stability throughout the ROM to prevent AP translation. On the lateral side, there is a lack of congruence allowing lateral femoral rollback in a manner close to the normal kinematic profile of the knee [26]. This specific design feature may confer the additional functional benefits seen in the MRK group.…”
Section: Discussionmentioning
confidence: 96%
“…Several authors analyzed ROM after arthroplasty with the use of the medial-pivot design and found a relationship between preoperative ROM and that obtained after surgery 4, 5, 23, 25, 26, 27. Shakespeare et al 28 compared 261 knees undergoing arthroplasty with medial-pivot prosthesis with 913 cases in which TKA with PCL sacrifice was performed.…”
Section: Discussionmentioning
confidence: 99%